4CPS-138 Biosimilars' utilisation under hospital pharmacy management policy. (March 2019) - Poitier, S; Machado, F; Figueira, A; Vandewalle, B; Andreozzi, V; Félix, J; Feio, J
Abstract : Background: Since October 2017 our university hospital implemented a Fully Integrated Biosimilars' utilisation management System (FIBS) managed by the hospital pharmacy. Purpose: To assess the effectiveness of hospital pharmacy management in the biosimilars policy and compare it to other similar public hospitals. Material and methods: FIBS is based on prescription and dispensing by international non-proprietary name. If biosimilars are available, the recommendations from the Hospital Medicines and Therapeutic Committee (HMTC) focus on the biologic drug with the best economic value. Non-biosimilar utilisation needs clinical justification on a patient-by-patient basis by prescribing physicians. The latter exceptions require validation by the Hospital board, HMTC and hospital pharmacy, which acts as a system gatekeeper. FIBS allow total traceability including biologic identification by tradename and batch number. Policy implementation was assessed by the extent of switching to, or initiation of, biosimilars by disease area. Policy effectiveness was assessed comparing our hospital biosimilars' utilisation benchmarked to other public hospitals with similar characteristics. Results: This analysis included all 718 patients using biologic therapy in rheumatic (31.3%), gastrointestinal (26.5%), haematologic (26.9%) and nervous system (11.1%) diseases and others (4.2%), since October 2017 when biosimilars for etanercept, infliximab and rituximab became available. Median follow-up time was 7.3 months. Switching to, or initiation of, biosimilars (SWT and INI) by disease area occurred in: rheumatic (84.9% and 6.7%), gastrointestinal (61.6% and 29.0%), haematologic (9.8% and 66.3%) and nervous system (60.0% and 15.0%) diseases and others (60.0% and 30.0%). The current overall proportion of patients in biosimilars' therapy was 85.2% and by biologic drug (SWT and INI): etanercept (82.6% and 9.8%), infliximab (69.7% and 22.2%) and rituximab (26.0% and 49.7%). Our hospital presented consistently higher rates of biosimilars' utilisation in comparison to other similar public hospitals: etanercept (92.4% vs 27.6%), infliximab (91.9% and 51.3%) and rituximab (75.7% and 35.1%). Conclusion: Hospital pharmacy management of the biosimilars policy was associated with substantial and rapid biosimilars' incorporation and utilisation. Our hospital has one of the best biosimilars' utilisation policy effectiveness in the country. References and/or acknowledgements: None to declare. No conflict of interest.